The role of providing modern equipment and the possibility of facilitating the task of paramedics - Mohammed Salem Hassan Al Yami,; Ali Mohammed Abdullah Alyami,; Faiz Dhafer Abdullah Al Shehri,; Muhammad Ismail Ali Al-Makarami,; Dafer Abdullah Alshehri,; Hamad Ali Al Zulig,; Abdullah Ahmed Awadh ALshehri,; Hadi Mana Hawam Al Mansour,; Saleh Ali Muta Al Khaerah,; Mohammed Dafir Faiz Al Shehri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The current study aimed to identify the role of medical equipment in helping paramedics to perform the roles required of them with a degree of quality through evaluating the tools and devices used in detection and in the initial diagnosis of cases in emergency situations. The results of the study showed that modern equipment is of great importance in helping paramedics through what these devices enable the paramedic in terms of methods and mechanisms for good diagnosis and, accordingly, writing good reports. The study recommends the necessity of paying attention to providing modern and advanced medical equipment and devices on a permanent basis.